(untitled) (Annals of Medical Research, 2021)
Aim: Current data regarding the relation between the Frontal QRS-T (FQRST) angle and the atherosclerotic burden is limited. This study purposed to investigate the relation between FQRST angle and the Syntax (SX) score in subjects presenting with STEMI. Material and Methods: Forty-nine patients who were admitted to the coronary care unit of a tertiary-care hospital for acute STEMI and underwent successful revascularization of the infarct related artery were included in this retrospective analysis. FQRST angle, QTc, and T peak- T end (TpTe) intervals were obtained from the presenting electrocardiogram (ECG). ECG was repeated 30 minutes after revascularization. The SX score was calculated using dedicated software. The study population was then divided into 3 tertiles based on the SYNTAX trial results as follows: SX score ≤ 22 (Low SX score, n=34), SX score ≥ 23 and 33 (Intermediate SX score, n=8), and those with an SX score ≥ 33(High SX score, n=7).Results: Median FQRST angle of the subjects with an SX score ≥ 33 was significantly wider than those with an SX score 22 had a longer TpTe interval than those with an SX score ≤ 22 points. SX score was significantly correlated with the FQRST angle (r=0.691, p 0.001) and TpTe interval (r=0.579, p 0.001).Conclusion: FQRST angle obtained from the admission surface ECG of the subjects with acute STEMI might reflect the extent and severity of the CAD, as demonstrated by the SX score. Moreover, FQRST angle may be useful in determination of the success of the revascularization in STEMI subjects.